Boards: Does one size fit all☆ - COLES, J; DANIEL, N; NAVEEN, L (Journal of Financial Economics, 2008)
This paper reexamines the relation between firm value and board structure. We find that complex firms, which have greater advising requirements than simple firms, have larger boards with more outside directors. The relation between Tobin's Q and board size is U-shaped, which, at face value, suggests that either very small or very large boards are optimal. This relation, however, arises from differences between complex and simple firms. Tobin's Q increases (decreases) in board size for complex (simple) firms, and this relation is driven by the number of outside directors. We find some evidence that R&D-intensive firms, for which the firm-specific knowledge of insiders is relatively important, have a higher fraction of insiders on the board and that, for these firms, Q increases with the fraction of insiders on the board. Our findings challenge the notion that restrictions on board size and management representation on the board necessarily enhance firm value.